Pengaruh Kurangnya Fasilitas Kantor terhadap Motivasi dan Kinerja Pegawai di Desa Tou Barat Kecamatan Kota Baru Kabupaten Ende - Mario Junior Anjelo; Yohanes Benediktus Bangu; Yeremias Bardi; Desideratio Primus Naitili; Anastasia Ata (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This study aims to determine the effect of inadequate office facilities on the motivation and performance of employees in Tou Barat Village, Kota Baru Subdistrict, Ende Regency. The main problem in this study is the limited work facilities such as computers, printers, photocopiers, internet networks, and uncomfortable working conditions, which will have an impact on the decline in employee motivation and work effectiveness. This study uses a descriptive qualitative method with a case study approach, through interviews, observation, and documentation to obtain in-depth data from employees and village management. The results of the study show that limited office facilities have a negative effect on the motivation, work enthusiasm, and productivity of employees. Employees often experience obstacles in completing tasks due to a lack of administrative and technological support facilities. However, employees try to adapt by using personal facilities such as laptops and private internet networks. This situation can create additional financial and psychological burdens and cause imbalances in work performance. Based on these findings, strategic measures are needed from the village government in the form of providing adequate office facilities, regular maintenance, technology training for employees, and the implementation of a digital work system. With improved facilities and a well-planned strategy, it is hoped that motivation, effectiveness, and the quality of public services in Tou Barat Village can be significantly improved.